Multifaceted prospects of nanocomposites for cardiovascular grafts and stents - Vellayappan MV (Dove Medical Press, 2015)
Muthu Vignesh Vellayappan,1 Arunpandian Balaji,1 Aruna Priyadarshini Subramanian,1 Agnes Aruna John,1 Saravana Kumar Jaganathan,1 Selvakumar Murugesan,2 Eko Supriyanto,1 Mustafa Yusof1 1IJN-UTM Cardiovascular Engineering Centre, Faculty of Biosciences and Medical Engineering, Universiti Teknologi Malaysia, Johor Bahru, Malaysia; 2Rubber Technology Center, Indian Institute of Technology, Kharagpur, India Abstract: Cardiovascular disease is the leading cause of death across the globe. The use of synthetic materials is indispensable in the treatment of cardiovascular disease. Major drawbacks related to the use of biomaterials are their mechanical properties and biocompatibility, and these have to be circumvented before promoting the material to the market or clinical setting. Revolutionary advancements in nanotechnology have introduced a novel class of materials called nanocomposites which have superior properties for biomedical applications. Recently, there has been a widespread recognition of the nanocomposites utilizing polyhedral oligomeric silsesquioxane, bacterial cellulose, silk fibroin, iron oxide magnetic nanoparticles, and carbon nanotubes in cardiovascular grafts and stents. The unique characteristics of these nanocomposites have led to the development of a wide range of nanostructured copolymers with appreciably enhanced properties, such as improved mechanical, chemical, and physical characteristics suitable for cardiovascular implants. The incorporation of advanced nanocomposite materials in cardiovascular grafts and stents improves hemocompatibility, enhances antithrombogenicity, improves mechanical and surface properties, and decreases the microbial response to the cardiovascular implants. A thorough attempt is made to summarize the various applications of nanocomposites for cardiovascular graft and stent applications. This review will highlight the recent advances in nanocomposites and also address the need of future research in promoting nanocomposites as plausible candidates in a campaign against cardiovascular disease. Keywords: nanocomposites, vascular grafts, stents, hemocompatibility, nanoparticles, cardiovascular biomaterials